Real-time MR elastography for viscoelasticity quantification in skeletal muscle during dynamic exercises - Schrank, Felix; Warmuth, Carsten; Goerner, Steffen; Meyer, Tom; Tzschaetzsch, Heiko; Guo, Jing; Uca, Yavuz Oguz; Elgeti, Thomas; Braun, Juergen; Sack, Ingolf (Magnetic Resonance in Medicine, 2020)
Purpose: To develop and test real-time MR elastography for viscoelastic parameter quantification in skeletal muscle during dynamic exercises. Methods: In 15 healthy participants, 6 groups of lower-leg muscles (tibialis anterior, tibialis posterior, peroneus, extensor digitorum longus, soleus, gastrocnemius) were investigated by real-time MR elastography using a single-shot, steady-state spiral gradient-echo pulse sequence and stroboscopic undersampling of harmonic vibrations at 40 Hz frequency. One hundred and eighty consecutive maps of shear-wave speed and loss angle (φ) covering 30.6 s of total acquisition time at 5.9-Hz frame rate were reconstructed from 360 wave images encoding 2 in-plane wave components in an interleaved manner. The experiment was carried out twice to investigate 2 exercises—isometric plantar flexion and isometric dorsiflexion—each performed over 10 s between 2 resting periods. Results: Activation of lower-extremity muscles was associated with increasing viscoelastic parameters shear-wave speed and φ, both reflecting properties related to the transverse direction relative to fiber orientation. Major viscoelastic changes were observed in soleus muscle during plantar flexion (shear-wave speed: 20.0% ± 3.6%, φ: 41.3% ± 12.0%) and in the tibialis anterior muscle during dorsiflexion (41.8% ± 10.2%, φ: 27.9% ± 2.8%; all P <.0001). Two of the muscles analyzed were significantly activated by plantar flexion and 4 by dorsiflexion based on shear-wave speed, whereas φ changed significantly in 5 muscles during both exercises. Conclusion: Real-time MR elastography allows mapping of dynamic, nonperiodic viscoelasticity changes in soft tissues such as voluntary muscle with high spatial and temporal resolution. Real-time MR elastography thus opens new horizons for the in vivo study of physiological processes in soft tissues toward functional elastography.
CRIS-Team Scopus Importer:2022-08-03
Keywords: activity patterns; dynamic exercise; real-time MRE; skeletal muscle function; stiffness; viscoelasticity